Synergy as a strategy to strengthen biomedical mentoring ecosystems - Packard, Becky Wai-Ling; Montgomery, Beronda L.; Mondisa, Joi-Lynn (Frontiers in Education, 2025)
Across science, technology, engineering, and math (STEM) fields, mentoring initiatives promote persistence among racially-diverse trainees within the biomedical workforce. Unfortunately, mentoring initiatives even within an individual college or university may be disconnected from one another, which can contribute to a lack of consistency and strategic investment. In this conceptual analysis, we argue for a synergistic strategy to biomedical mentoring, which involves rethinking disconnected approaches to mentoring and moving toward a systems design approach for strengthening the infrastructure. We offer our STEM mentoring ecosystems framework, which helps institutions survey the landscape, take stock of assets, “connect the dots” of exemplary programs and initiatives, and identify gaps and vulnerabilities in mentoring ecosystems. Action planning should involve seeking strategic synergy by bringing intentionality to the interdisciplinary collaborations common within biomedical contexts. We unpack the concept of synergy, illustrate synergy within a biomedical context, and outline multiple pathways to synergy. Readers are invited to consider ways to optimize their biomedical mentoring ecosystems using synergistic strategy as they aim to diversify and strengthen the biomedical workforce.